Within-Host Microevolution of Pseudomonas aeruginosa Urinary Isolates: A Seven-Patient Longitudinal Genomic and Phenotypic Study - Cottalorda, Agnès; Leoz, Marie; Dahyot, Sandrine; Gravey, François; Grand, Maxime; Froidure, Thomas; Aujoulat, Fabien; Le Hello, Simon; Jumas-Bilak, Estelle; Pestel-Caron, Martine (Frontiers in Microbiology, 2021)
Background Pseudomonas aeruginosa is responsible for up to 10% of healthcare associated urinary tract infections (UTI), which can be difficult to treat and can lead to bacterial persistence. While numerous whole genome sequencing (WGS) analyses have explored within-host genomic adaptation and microevolution of P. aeruginosa during cystic fibrosis (CF) infections, little is known about P. aeruginosa adaptation to the urinary tract. Results Whole genome sequencing was performed on 108 P. aeruginosa urinary isolates, representing up to five isolates collected from 2 to 5 successive urine samples from seven patients hospitalized in a French hospital over 48–488 days. Clone type single nucleotide polymorphisms (ctSNPs) analysis revealed that each patient was colonized by a single clone type (<6000 SNPs between two isolates) at a given time and over time. However, 0–126 SNPs/genome/year were detected over time. Furthermore, large genomic deletions (1–5% of the genome) were identified in late isolates from three patients. For 2 of them, a convergent deletion of 70 genes was observed. Genomic adaptation (SNPs and deletion) occurred preferentially in genes encoding transcriptional regulators, two-component systems, and carbon compound catabolism. This genomic adaptation was significantly associated with a reduced fitness, particularly in artificial urine medium, but no strict correlation was identified between genomic adaptation and biofilm formation. Conclusion This study provides the first insight into P. aeruginosa within-host evolution in the urinary tract. It was driven by mutational mechanisms and genomic deletions and could lead to phenotypic changes in terms of fitness and biofilm production. Further metabolomic and phenotypic analyses are needed to describe in-depth genotype-phenotype associations in this complex and dynamic host-environment.